ORIGINAL ARTICLE: CLINICAL PROFILE AND EPIDEMIOLOGICAL ASPECTS OF DIPHTHERIA CASES IN RUANG ISOLASI KHUSUS RSUD DR SOETOMO FROM JANUARY UNTIL DECEMBER 2015 - Andi Airina Binti A Agus; Dominicus Husada; Pudji Lestari (Universitas Syiah Kuala, 2019)
Abstract. Background Diphtheria is a vaccine-preventable disease and is eradicated mostly in developed countries. But the prevalence of diphtheria cases still remains endemic in developing countries such as Indonesia, mainly in East Java. Purpose: To study the clinical profile and epidemiological aspects of diphtheria cases admitted in Ruang Isolasi Khusus RSUD Dr. Soetomo in 2015. Method: This research is a hospital-based, cross-sectional study. The samples are all patients admitted in Ruang Isolasi Khusus RSUD Dr Soetomo with the diagnosis of diphtheria in 2015. Results: There were 23 diphtheria cases reported in Ruang Isolasi Khusus RSUD Dr. Soetomo in 2015. The most prevalent age group was 6 until 10 years old (56.52%) and the most common gender was male (57%). Most of the patients came from a non-endemic area (82.61%) and most of them are not fully vaccinated (73.91%). There are more unknowledgeable mothers (91%) about DPT immunization. The most prevalent clinical manifestations are fever, dysphagia and pseudomembrane (100%). Tonsillar diphtheria (86.96%) was the most prevalent type of diphtheria presented. There were no complications and mortality reported and the main managements used were isolation (100%), antibiotics (100%) and anti diphteria serum (82.61%). Conclusion: There is an age shift in the occurrence of diphtheria to 6 until 10 years of age. The immunization coverage especially the booster dose is still low among the patients. Less knowledge about DPT immunization contributes to low childhood immunization coverage. No complications and mortality reported.